HUMAN RESOURCES FACTORS AFFECTING INCREASING LABOR PRODUCTIVITY IN CONSTRUCTION PROJECTS IN EAST NUSA TENGGARA - Alva Yuventus Lukas; Jusuf Wilson Meynerd Rafael (Journal Innovation of Civil Engineering (JICE), 2020)
The purpose of this study is to determine the resource management factors that affect labor productivity as well as the dominant factors, with research sites on construction projects in eastern Indonesia, particularly in East Nusa Tenggara. This research is aimed at construction workers, such as masons, chief craftsmen, foremen, and workers. This study uses a survey method. Primary data were collected through a questionnaire, then formulated and processed. Data processing in the form of respondents' opinions and attitudes towards problems that exist in construction projects related to productivity, data analysis techniques use factor analysis methods and multiple linear regression analysis with the SPSS statistical program. Results of processing and discussion of data, it is found that : (A) Human Resource Management Factors that affect Labor Productivity in several construction projects in East Nusa Tenggara are About Age, X1, about Work Experience, X2, Level of Education, X3,  about Wages, X4, Total Family Count, X5, Working Health and Safety, X6, Relationship Workers, X7, about Managerial, X8, and about Influential Motivations, X9, together form the equation Y = 12,776 – 0,217.X1 + 0,151.X2 – 0,087.X3 - 0,074.X4 - 0,263.X5 - 0,468X6 - 0,058.X7 + 0,129.X8 + 0,384.X9 .    (B)  The dominant factors affecting respectively are the Occupational Health & Safety of Workers, X6, Subject to the Number of Dependents in the Family, X5, and Subjects of Motivation, X9.